2019
DOI: 10.1103/physrevb.100.054506
|View full text |Cite
|
Sign up to set email alerts
|

Electrical control of magnetization in superconductor/ferromagnet/superconductor junctions on a three-dimensional topological insulator

Abstract: Strong dependence of the Josephson energy on the magnetization orientation in Josephson junctions with ferromagnetic interlayers and spin-orbit coupling opens a way to control magnetization by Josephson current or Josephson phase. Here we investigate the perspectives of magnetization control in superconductor/ferromagnet/superconductor (S/F/S) Josephson junctions on the surface of a 3D topological insulator hosting Dirac quasiparticles. Due to the spin-momentum locking of these Dirac quasiparticles a strong de… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 63 publications
(66 reference statements)
0
24
0
Order By: Relevance
“…Second period doubling is observed at G = 7.9 (period-4 (P4) motion). Then, chaotic bands can be observed at the intervals [8, 11.5] and [16,20], with the periodic motion in between. The system demonstrates a bistable state (BS), two points with the same value, but different signs, for m x and m y within the intervals [12.7, 16] and [30, 43.5],…”
Section: A Dynamical Effects At ωJ =mentioning
confidence: 99%
See 1 more Smart Citation
“…Second period doubling is observed at G = 7.9 (period-4 (P4) motion). Then, chaotic bands can be observed at the intervals [8, 11.5] and [16,20], with the periodic motion in between. The system demonstrates a bistable state (BS), two points with the same value, but different signs, for m x and m y within the intervals [12.7, 16] and [30, 43.5],…”
Section: A Dynamical Effects At ωJ =mentioning
confidence: 99%
“…The nonlinear dynamics of the JJ is sensitive to the orientation of the magnetization [16,[25][26][27][28][29][30][31], and a rich physics has been predicted due to this type of coupling between the Josephson and magnetic subsystems: for example, supercurrent-induced magnetization dynamics [25,32,33]. In the NM-JJ system, the reversal of the magnetic moment by the supercurrent pulse [30], the appearance of Devil's staircase [24] and Kapitza pendulum effects [11,34,35], have been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…( 8). For the case of the combined F/TI interlayer both the critical current j c and the anomalous ground state phase shift χ 0 are sensitive to the magnetization dynamics and for the temperatures close to the critical temperature T c are written as follows 29 :…”
Section: Electrical Detection Of Magnetization Reversalmentioning
confidence: 99%
“…Spin-orbit effects have been discussed actively in the framework of the quasiclassical Green's functions approach in layered structures. 17,18,[38][39][40][41][42][43][44][45] Recently, the generalized quasiclassical theory was developed for a twodimensional system with SOC and an exchange field both much greater than the disorder strength. 46 It has been shown that spontaneous supercurrent can flow in a Josephson junction, where magnetized superconductors are weakly coupled through the surface of 3D TI.…”
Section: Introductionmentioning
confidence: 99%